Determinación de la capacidad infecciosa de Tagosodes Orizicolus (Muir), vector del Vhba mediante la prueba de la planta susceptible en el Valle del Bajo Mayo - Mera Saavedra, Benjamín (2010)
The present work “Determination of the infectious capacity of Tagosodes orizicolus (Muir), vector of the VHBA by means of the test of the susceptible plant (Echinochloa sp) in the valley of the first floor May”.; I use the objective of determining the infectious capacity of the population of Tagosodes orizicolus, Vector of the VHBA using like susceptible plant to Echinochloa sp. in the Valley of the First floor May, San Martin; the present investigation work one carries out in the hothouse of the Ability of Agrarian Sciences of the National University of San Martin. You uses the design Totally at random (DCA), with 23 treatments and 03 Observations. The treatments were the committees of regantes of the whole valley of the first floor May T1 (Moral), T2 (Union Cocopa), T3 (Rosanaico), T4 (First of October), T5 (Cumbacillo) T6 (Cachaboya), T7 (I Triumph), T8 (Future), T9 (Saint John the Baptist), T10 (High Chupishiña) T11 (Low Chupishiña), T12 (Santa Rosa of cumbaza), T13 (San Juan of Cumbaza), T14 (San Rafael), T15 (San Martin of cumbaza) T16 (Pacaya), T17 (Juan War), T18 (Chupishiña), T19 (Shucushco), T20 (Capironaico) T21 (Shilcayo Chontamuyo), T22 (Ahuashiyacu) and T23 (Beautiful Horizon). The results demonstrated that the biggest percentages of incidence and severity of the BHVA in Echinochloa Sp, was obtained of the populations Tagosodes sp. of the sector Morales and the but low incidence corresponds to the sector Capironaico.